Responses of physiological groups of tropical heterotrophic bacteria to temperature and dissolved organic matter additions: food matters more than warming - Morán, Xosé Anxelu G. (Environ Microbiol, 2020)
Compared to higher latitudes, tropical heterotrophic bacteria may be less responsive to warming because of strong bottom‐up control. In order to separate both drivers, we determined the growth responses of bacterial physiological groups to temperature after adding dissolved organic matter (DOM) from mangroves, seagrasses and glucose to natural seawater from the Great Barrier Reef. Low (LNA) and high (HNA) nucleic acid content, membrane‐intact (Live) and membrane‐damaged (Dead) plus actively respiring (CTC+) cells were monitored for 4 days. Specific growth rates of the whole community were significantly higher (1.9 day(‐1)) in the mangrove treatment relative to the rest (0.2–0.4 day(‐1)) at in situ temperature and their temperature dependence, estimated as activation energy, was also consistently higher. Strong bottom‐up control was suggested in the other treatments. Cell size depended more on DOM than temperature. Mangrove DOM resulted in significantly higher contributions of Live, HNA and CTC+ cells to total abundance, while the seagrass leachate reduced Live cells below 50%. Warming significantly decreased Live and CTC+ cells contributions in most treatments. Our results suggest that only in the presence of highly labile compounds, such as mangroves DOM, can we anticipate increases in heterotrophic bacteria biomass in response to warming in tropical regions.